The general principles of vicarious liability in Malaysia / Mariam Isa - Isa, Mariam (Faculty of Law, 1985)
English common law. formed part of the laws in Malaysia and the authority for the reception of this law of England into this country is provided under Section 3 of the Civil Law Act 1956 (Revised 1972). Vicarious liability was first instituted in England and the law relating to vicarious liability has since undergone changes such that the employer's vicarious liability is being extended while the servant IS liability is correspondingly shrinking. The shifting of liability from the employee to the employer is justified because of a great increase of potential sources of harm and due to the rapid growth of industralisation that the employer is a far more superior position to bear the losses. The ambit of vicarious liability is expanding and this can be seen from the various types of relationship that tend to create liability and it extended for the torts of independent contractors. Even though employers can be vicariously liable certain defences are available for them but these defences have some lost its importance and some have been reduced e. g. common employment was abolished by statute. All this is to protect the workmen. In Malaysia, social insurance takes the form of workmen I s compensation and employees social security provided by statutes which are the Workmen I s Compensation Act 1957 and Employees Social Security (Amended) Act 1984.